ASSOCIATION OF ASYMPTOMATIC TARGET ORGAN DAMAGES WITH SECRETED FRIZZLED RELATED PROTEIN 5 IN THE ELDERLY: THE NORTHERN SHANGHAI STUDY. (June 2018) - Teliewubai, J.; Bai, B.; Lu, Y.; Zhou, Y.; Yu, S.; Chi, C.; Xu, Y.; Zhang, Y.; Ji, H.
Abstract : Objective: Secreted frizzled related protein 5 (SFRP5) is a novel anti-inflammatory adipokine which is implicated in metabolic and cardiovascular disease (CVD). However, little is known about the relevance of SFRP5 with asymptomatic hypertensive target organ damages (TOD). We aimed to investigate the association between SFRP5 and TOD in a large population study. Figure. No caption available. Design and method: Associations between plasma SFRP5 and cardiovascular risk factors as well as TOD were investigated in 1745 participants from Northern Shanghai Study. Plasma SFRP5 level was measured by an enzyme-linked immunosorbent assay. Results: Plasma SFRP5 level was negatively associated with body mass index, waist/hip ratio and fasting blood glucose (all P < 0.001). Lower plasma SFRP5 level was observed in men than in women (4.19 vs 5.13 ng/ml, P < 0.001), in smokers than in nonsmokers (4.34 vs 4.78 ng/ml, P < 0.05). Additionally, plasma SFRP5 level was also lower in diabetes than those without diabetes (4.30 vs 4.81 ng/ml, P < 0.05). Further, an inverse association was observed between SFRP5 and pulse wave velocity as well as carotid intima-media thickness (both P < 0.05). Moreover, multivariate logistic regression analysis showed lower SFRP5 level was associated with increased arterial stiffness in the elderly (OR 0.83, 95% CI 0.71 to 0.99 per 1-SD increase, P < 0.05). Conclusions: Plasma SFRP5 level was inversely correlated with conventional cardiovascular risk factors and low plasma SFRP5 was also significantly associated with arterial stiffening in the elderly Chinese population.